Internet of things: The future and challenges for epidemiology and public health - Rodríguez-Gómez, Rodolfo (Universidad y Salud, 2019)
Introduction: Internet is living one of the greatest revolutions in history called Internet of things. Both epidemiology and public health have great potential in it since the new hyperconnected world will represent spaces for the reinvention and innovation never before imagined in various aspects of the health field. Objective: To reflect on the possibilities for epidemiology and public health in the scenario of the Internet of things. Materials and methods: Documentary review that included physical texts and electronic databases. Results: Internet of things represents for epidemiology and public health, a dimension full of opportunities due to the massive data sources and technologies of the fourth industrial revolution, but also new challenges, mainly in terms of security and privacy of information. Conclusions: The age of Internet of things has opened up the possibility of multiple data sources, many in real time, for epidemiology and public health. This will facilitate the optimization of the perspective and understanding of multiple health events and the achievement of more proactive and predictive health care.